Use of Rubber Trees (Havea brasiliensis) Tube Fermentated by using Rumen Cow in feed for Growth of Asian Redtail Catfish (Hemibagrus nemurus) - Roy Andre Parsaoran Manurung; Adelina Adelina; Indra Suharman (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2023)
This research was conducted at the Fish Nutrition Laboratory and Experimental Reservoir of the Faculty of Fisheries and Marine, University of Riau which was carried out from June to August 2021. This study aims to determine the effect of the use of rubber seed flour which is fermented using cow rumen fluid for the growth of tropical catfish (Hemibagrus nemurus) fry. This study used a Complete Randomized Design (RAL) with 5 levels of treatment and 3 repeats. The tropical catfish fry used had an average weight of 0.67 ± 0.07 g. Test fish were put into the cage am with a stocking density of 25 heads. The test feed used is in the form of pellet with a protein content of 37.71-38.92%. The treatment in this study was in the form of the use of fermented rubber seed flour in the feed by 0.5, 10, 15, 20%. Test feed is given as much as 10% of the weight of biomass with a frequency of feeding 3 times a day, feeding is carried out for 56 days. To measure the digestibility of fish feed, feed is given containing Cr2O3 as much as 0.5% of the amount of feed. Test fish weighing 0.67 ± 0.07 g are introduced into the aquarium with a stocking density of 10 heads. After feeding, fish feces are collected and dried to measure cr 2O3 levels and their proteins. The results of this study showed that the best treatment was found in P2, the use of 35% fermented rubber seed flour which resulted in 77.27% feed digestibility, 82.64% protein digestibility, 53.59% feed efficiency, 30.53% protein retention, 4.14% specific growth rate and 98.66% dilution.